Assessing early childhood developmental functioning in the parental screening tool: an application of the Rasch model - Lucia Ráczová; Tomáš Urbánek; Erika Jurišová; Marta Popelková; Tomáš Sollár (Frontiers in Psychology)
ObjectivesEnsuring rapid and efficient detection of developmental difficulties in early childhood necessitates aligning screening tools with the timing of preventive examinations in each country, emphasizing the need for quick and effective unidimensional screening methods.AimThis study aims to assess the scalability and unidimensionality of developmental functioning in two- and three-year-old children using Guttman scaling and the Rasch model.MethodsThe anonymized data from 1,640 children aged 26 to 44 months, whose caregivers completed the S-PMV11 method, were gathered from routine pediatric preventive check-ups via the National Database.ResultsThe findings indicate the effective scalability of developmental functioning using the Guttman approach, thus enabling the early identification of children at risk. Additionally, the Rasch model confirms the unidimensionality of developmental functioning, highlighting the importance of early intervention addressing.ConclusionDespite the instrument’s construct validity, significant concerns arise regarding its ability to capture children with borderline developmental functioning. These concerns could be addressed and improved by simply organizing the items by difficulty level in the pediatric response sheet, allowing the pediatrician to effectively identify any early signs of developmental issues.